Characterization of polymethyl methacrylate / feather fiber / montmorillonite composites for dental post application - Salehuddin, Siti Maizatul Farhain (2015)
The aim of this study was to explore the potential of the goose feather fiber for the development of dental post for the treatment of pulpless teeth. In this research, polymethyl methacrylate (PMMA), feather fiber (FF), glass fiber (GF) and montmorillonite (MMT) composites were prepared using Brabender internal mixer. FF/PMMA and GF/PMMA composites were produced in the range of 1, 3, 5, 7 and 10 phr composition of feather and glass fiber respectively while FF/PMMA/MMT and GF/PMMA/MMT composites were produced in the range of 1, 3, 5, 7 and 10 phr composition of feather and glass fiber with the addition of 4 wt % of MMT. The performance of FF/PMMA was compared with GF/PMMA composites. The mechanical properties of composites were studied through the flexural test. The changes on the glass transition temperature (Tg) and thermal stability of composites was studied through differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). Morphology of the composites was analyzed using scanning electron microscope (SEM) and transmission electron microscopy (TEM). The chemical structure of composites was studied by using Fourier transform infrared (FTIR) spectroscopy. The structural characterization of silicate layer was investigated using X-ray diffraction (XRD). Biological properties were determined through in-vitro cytotoxicity test to demonstrate the biocompatibility of the composites. The result of flexural properties of FF/PMMA and GF/PMMA composites showed the addition of FF and GF significantly increased the strength and stiffness of composites. The composites containing 10 phr of both fiber had the highest flexural strength and modulus. Similar result was obtained for FF/PMMA/MMT and GF/PMMA/MMT composites. DSC results showed that the Tg of the PMMA matrix increased with increasing of fiber loading. The incorporation of MMT on FF/PMMA and GF/PMMA composites exhibited higher rigidity on the chain of the composites significantly. TGA curves exhibited a significant improvement in thermal stability for FF/PMMA/MMT and GF/PMMA/MMT composites with the incorporation of MMT. SEM analysis of the composites showed a relatively uniform distribution of the fiber in the polymer matrix and compatibility between the matrix and fiber. The TEM image showed that the presence of exfoliated structure in FF/PMMA/MMT and GF/PMMA/MMT composites. In-vitro cytotoxicity test of the composites showed no noticeable cytotoxicity indicated the excellent biocompatibility in biological properties of composites.